A Cross-Recurrence Analysis of the Pupil Size Fluctuations in Steady Scotopic Conditions - Piu, Pietro; Serchi, Valeria; Rosini, Francesca; Rufa, Alessandra (Frontiers in Neuroscience, 2019)
Pupil size nonlinearly fluctuates during stationary scotopic conditions and conveys information about the activity in the autonomic nervous system. In this study the frequency spectrum of the pupil signal was firstly obtained by empirical mode decomposition. Cross-recurrence quantification analysis was then used to unfold the nonlinear dynamics of the low- and high-frequency coupled oscillators in the autonomic spectrum (0-0.45 Hz). The global and local patterns of recurrence of their trajectories in the phase space were estimated by two parameters: determinism and entropy. The main purpose was to provide normative health-related values of entropy and determinism. An elliptic region in the entropy-determinism plane, which spanned the 95 % prediction area, yielded the normative values. Therefore, data points inside the ellipse would likely represent balanced activations in the autonomic nervous system. Interestingly, there was also evidence that the Epworth sleepiness scores scaled up along with entropy and determinism. This finding suggested that our procedure might help to support clinical assessments in several pathologies related to impairments in the autonomic nervous system. Although other nonlinear methods like short time Fourier transform and wavelets transformations are usually applied for analyzing the pupillary oscillations, they still rely on strong assumptions like the stationarity of the signal or the a priori knowledge of the shape of the single basis wave. Instead, the cross-recurrence analysis of the nonlinear dynamics of the pupil size oscillations is an adaptable diagnostic tool for identifying alertness and/or pathological status.